The first year experience in Australian universities findings from 1994 to 2009 - James, Richard; Jennings, Claire; Krause, Kerri-Lee Dawn.; University of Melbourne. Centre for the Study of Higher Education (Melbourne : University of Melbourne, Centre for the Study of Higher Education, 2009)
"The 2009 First Year Experience survey is the fourth national study undertaken by the Centre for the Study of Higher Education at five-yearly intervals since 1994. This report therefore presents findings on the changing attitudes and experiences of first year students in Australian universities across a period of 15 years. Longitudinal datasets of this kind are rare in Australian higher education."
Title from screen (viewed on 25 May 2010).
Bibliography: p. 75.
Text.
Mode of access : Internet via World Wide Web. Available at: http://www.cshe.unimelb.edu.au/research/FYE_Report_1994_to_2009.pdf
System requirements: Adobe Acrobat reader required to view/print pdf files.
Selected for archiving
Keywords: Education, Higher -- Statistics; Education, Higher -- Research -- Australia; Education, Higher -- Australia